DAMPAK PEMBELAJARAN DARING BAGI SISWA SMA SELAMA COVID-19 DI KECAMATAN CIKEUSAL KAB. SERANG-BANTEN - Indriyani, Indriyani; Hardiansyah, Muhammad Agus (Universitas Tanjungpura, 2022)
This study aims to determine the impact that occurs on high school students with learning used in modern times at this time. In modern times, more use of internet learning media or commonly called learning media boldly. Brave learning is learning that uses internet media so that students do not directly meet face to face in the same place as educators. This study used qualitative research methods. Qualitative research method is descriptive research. In this study, researchers directly observed and conducted interviews with informants and developed the information that had been obtained. The object of this research is high school students in Cikeusal district, Serang district. The results in this study contain the impact felt by every high school student when using online learning such as boredom in learning, not getting the maximum subject matter, lazy to interact directly, not focused, often late, easier to cheat and early marriage. So that educators are expected to be able to evaluate and change learning to be even better than before.